Mortality rate of percutaneous coronary interventions in ST-segment elevation myocardial infarction patients under the public health insurance schemes of Thailand - Chumsantivut, Suppavit; Lertmaharit, Somrat; Rattananupong, Thanapoom; Lertsuwunseri, Vorarit; Athisakul, Siriporn; Wanlapakorn, Chaisiri; Srimahachota, Suphot (Frontiers in Cardiovascular Medicine, 2024)
This article is provisionally accepted.